Developing students' energy literacy in higher education. Issue 4 (6th July 2015) - Cotton, Debby R E; Miller, Wendy; Winter, Jennie; Bailey, Ian; Sterling, Stephen
Abstract : Purpose: – This paper aims to investigate students' energy literacy at a UK university, and recommends ways in which it can be enhanced using a behaviour change model. Developing students' energy literacy is a key part of the "greening" agenda, yet little is known about how students develop their ideas about energy use and energy saving at a university. Design/methodology/approach: – The research utilised a mixed-methods approach including an online survey (with 1, 136 responses) and focus groups. Findings: – The research identified strengths and weaknesses in students' energy literacy, and noted the relative influence of formal and informal curricula. The potential for aligning these curricula is highlighted through the 4Es model of enable, engage, exemplify and encourage. Research limitations/implications: – The research involved a single instrumental case-study site. The wider applicability of the findings should therefore be tested further in other institutions. Practical implications: – The research suggests ways in which universities might better support their students in making more sustainable energy-related behaviour choices, and it indicates the importance of knowledge as well as attitudes. Social implications: – The research may have implications for the energy-saving behaviours of individuals in the wider society. Originality/value: – Attempts to reduce energy use in higher education are widely seen in campus operations. This research provides an indication of the potential for enhancing energy-saving through different forms of curricula.